DETEKSI TINGKAT KEMIRIPAN DATA SISWA PESERTA UJIAN BERBASIS KOMPUTER PADA BIMBINGAN BELAJAR EXPERT DENGAN MENGGUNAKAN METODE LEVENSHTEIN DISTANCE - Guntur Syahputra; Jijon Raphita Sagala (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2017)
In the world of education evaluation is mandatory to measure the level of success educational process. Computer-based Test often make students fail because of incorrect filling of biodata. This research to measure the level of similarity student identity so small mistake made by participants can be tolerated by the computer when filling of biodata and ultimately can reduce the failure rate of computer-based Test participants. This research is very important considering the change of Study methods this time to using of technology. By using approach of Levenshtein Distance method can detect the resemblance of biodata of exam participants so that when seen there is similarity it can improve the writing of wrong data. By implementing this method into the problem correction application according to the needs of the system in Bimbel Expert.Keywords : Levenstain Distance, Similarity Of Data, Examination.